X2+11x+11 = 7x+9 X2+11x-7x+11-9 = 0 x2+4x+2 = 0 Solve as a quadratic equation by using the quadratic equation formula or by completing the square: x = -2 + or - the square root of 2
If 6x + 10 = 11x , then x=2.
x2+11x+11 = 7x+9 x2+11x-7x+11-9 = 0 x2+4x+2 = 0 The above quadratic equation can be solved by using the quadratic equation formula and it will have two solutions.
The discriminant is 0.
11x = 20x +1811x-20x=18x(11-20)=18-9x=18x=-2
7x + 8 = 11x + 3, solve for xsubtract 7x from both sides8 = 11x - 7x + 38 = 5x + 3subtract 3 from both sides5 = 5xdivide both sides by 51 = x.
2x = 11x + 4 Subtract 11x from both sides: -9x = 4 Divide both sides by -9: x = 4/(-9) = -0.444...
12x = 11x - 5, subtract both sides by 11x x = -5
(11 plus or minus the square root of 129) divided by 4x = 5.589454172900137x = -0.0894541729001368
Does it say solve for y?
It is B, 0.